The Effect of Workplace Spirituality, Organizational Citizenship Behavior, Quality of Work-Life on Turnover Intention with Job Satisfaction as a Mediation: Study in Indonesian Aircraft Maintenance Industry PT GMF Aeroasia TBK - Syahrul, Hermawan; Nurjanah, Siti; Parimita, Widya (Journal of Ecohumanism, 2024)
The purpose of this study was to analyze the influence of workplace spirituality, organizational citizenship behavior, quality of work life and job satisfaction, on turnover intention directly and indirectly. This research was a quantitative study with a sample of 267 employees of the engine service division of PT GMF AeroAsia. The sampling technique used was purposive sampling. The results of the study found: 1) there is a direct influence of workplace spirituality on job satisfaction, 2) there is no direct influence of organizational citizen behavior on job satisfaction, 3). there is a direct influence of quality of work life on job satisfaction, 4) there is a direct influence of workplace spirituality on turnover intention, 5) there is no direct influence of organizational citizen behavior on turnover intention, 6) there is a direct influence of quality of work life on turnover intention, 7) there is a direct influence of job motivation on turnover intention, 8) there is an indirect influence of workplace spirituality on turnover intention through job satisfaction, 9) there is no indirect influence of organizational citizen behavior on turnover intention through job satisfaction, 10) there is an indirect influence of quality of work life on turnover intention through job satisfaction.